2016
DOI: 10.1002/gj.2858
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology, geochemistry and tectonic implications of Weitingchagan composite pluton in northern segment of the Xing‐Meng Orogenic Belt

Abstract: We undertook zircon U–Pb dating and geochemical analyses of the Weitingchagan (WT) pluton in the Dong Ujimqi area, Northeast China, with an aim of determining their ages, petrogenesis and sources, which are important for understanding the Late Palaeozoic tectonic evolution of the Xing‐Meng Orogenic Belt. The WT pluton consists of coarse‐ to medium‐grained porphyritic granites in the core and medium‐ to fine‐grained monzogranites in the rim, contains abundant microgranular enclaves and is intruded by small amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…In combination with our new LA‐ICP‐MS U–Pb ages from the QJC pluton, we suggest that the pluton is a composite pluton composed of two phases of magmatic activities in XMC, with the ages of 300~312 Ma and ~280 Ma. In the near area, such as the Uliastai continental margin, the magmatic activities during the Carboniferous to the Permian also is characterized by two phases (Liu et al, ; Tong et al, ; Xin, Teng, & Cheng, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…In combination with our new LA‐ICP‐MS U–Pb ages from the QJC pluton, we suggest that the pluton is a composite pluton composed of two phases of magmatic activities in XMC, with the ages of 300~312 Ma and ~280 Ma. In the near area, such as the Uliastai continental margin, the magmatic activities during the Carboniferous to the Permian also is characterized by two phases (Liu et al, ; Tong et al, ; Xin, Teng, & Cheng, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…2004; Liu et al . 2019). According to the results of previous research, some Early Cretaceous A-type granites and alkaline rocks have been reported in the Liaoning Peninsula – for example, Qianshan granite (127 Ma), Taipingshan alkaline feldspar granite (129 Ma), Guanmenshan Granite porphyry (126 Ma) and quartz syenite (127 Ma) – which indicate that the Liaodong Peninsula existed in an extensional tectonic setting (Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…2007 a , b ; Liu et al . 2016, 2019). Metamorphic core complexes (MCC) are also widely developed in the Liaoning Peninsula; for example, the Yinmawan (129–120 Ma) and Gudaoling (127–118 Ma) plutons were emplaced along the detachment fault of the Liaonan–Wanfu MCC (130–113 Ma), which was in an extensional tectonic environment (Guan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Nb‐Ta and Zr‐Hf relations have been employed as a useful tool to trace magma sources (Dostal & Chatterjee, ; Green, ; Liu et al, ; McCulloch & Gamble, ). The Nb/Ta (8.91–10.00, average: 9.56) and Zr/Hf (18.98–24.66, average: 20.77) ratios of the volcanic rocks are closer to those in the crust (11.4 and 33, respectively) than primitive mantle (17.8 and 37, respectively).…”
Section: Discussionmentioning
confidence: 99%